Pelatihan Integrasi Media Digital dalam Empat Keterampilan Bahasa Mandarin (数字化媒体在汉语听说读写技能中的应用) Bagi Guru-Guru Bahasa Mandarin - Karina Fefi Laksana Sakti; Amira Eza Febrian Putri; Aiga Ventivani; Tegas Trista Atma Putra; Nabilla Zahira Shofa; Lambang; Marsella; Farid Dwi Hardianto; Faris Rullyanto (FKIP Universitas Mataram, 2026)
Appropriate use of instructional media is one of the important aspects in creating an effective, engaging, and learner-centered learning process. In Mandarin language learning, the availability of relevant instructional media remains relatively limited, particularly media that can be optimally utilized by teachers and students in Indonesia. Most available resources and media are still dominated by materials in Mandarin, which have not fully met the needs of learning in various school contexts. Based on this condition, the training was organized with the aim of expanding alternative Mandarin learning media while also improving teachers’ competence in developing digital instructional media. This activity focused on training in the integration of digital media into the learning of the four Mandarin language skills (数字化媒体在汉语听说读写技能中的应用) for Mandarin teachers in the Greater Malang area as an effort to support a more innovative and interactive learning process. The implementation method used was a mentoring approach consisting of the stages of planning, implementation, and evaluation. The results showed that the training was carried out successfully and received positive responses from the participants. Furthermore, the training was proven to be beneficial in improving teachers’ ability to design digital teaching materials that are appropriate to the needs of Mandarin language learning.